Inhibition of Glutamine Uptake Improves the Efficacy of Cetuximab on Gastric Cancer - Huanrong Ma PhD; Jingjing Wu Bachelor; Minyu Zhou PhD; Jianhua Wu PhD; Zhenzhen Wu PhD; Li Lin PhD; Na Huang PhD; Wangjun Liao PhD; Li Sun PhD (Integrative Cancer Therapies)
Treatment for advanced gastric cancer is challenging. Epidermal growth factor receptor (EGFR) contributes to the proliferation and development of gastric cancer (GC), and its overexpression is associated with unfavorable prognosis in GC. Cetuximab, a monoclonal antibody targeting EGFR, failed to improve the overall survival of gastric cancer patients indicated in phase III randomized trials. Glutamine is a vital nutrient for tumor growth and its metabolism contributes to therapeutic resistance, making glutamine uptake an attractive target for cancer treatment. The aim of the present study was to investigate whether intervention of glutamine uptake could improve the effect of cetuximab on GC. The results of MTT assay showed that by glutamine deprivation or inhibition of glutamine uptake, the viability of gastric carcinoma cells was inhibited more severely than that of human immortal gastric mucosa epithelial cells (GES-1). The expression of the key glutamine transporter alanine-serine-cysteine (ASC) transporter 2 (ASCT2; SLC1A5) was significantly higher in gastric carcinoma tissues and various gastric carcinoma cell lines than in normal gastric tissues and cells, as shown by immunohistochemistry and western blotting, while silencing ASCT2 significantly inhibited the viability and proliferation of gastric carcinoma cells. Consistent with previous studies, it was shown herein by MTT and EdU assays that cetuximab had a weak inhibitory effect on the cell viability of gastric carcinoma cells. However, inhibiting glutamine uptake by blockade of ASCT2 with l -γ-glutamyl- p -nitroanilide (GPNA) significantly enhanced the inhibitory effect of cetuximab on suppressing the proliferation of gastric cancer both in vitro and in vivo . Moreover, combining cetuximab and GPNA induced cell apoptosis considerably in gastric carcinoma cells, as shown by flow cytometry, and had a higher depressing effect on gastric cancer proliferation both in vitro and in vivo , as compared to either treatment alone. The present study suggested that inhibition of glutamine uptake may be a promising strategy for improving the inhibitory efficacy of cetuximab on advanced gastric cancer.